Prevalence of hypothyroidism in a dyslipidemic population over age 35 in Manizales, Colombia - José Henry Osorio; César Augusto Aguirre (Revista de la Facultad de Medicina, 2016)
Introduction: The thyroid hormone acts as a regulator of lipids in metabolism and can affect the development of cardiovascular diseases and dyslipidemia.